THE SIMULATION OF SKEG EFFECT TO BARGE RESISTANCE CALCULATION USING CFD-RANS OPENFOAM - Abrari Noor Hasmi; Samsu Dlukha Nurcholik (Wave: Jurnal Ilmiah Teknologi Maritim, 2020)
The paper discusses the significance of different types of skegs in a barge toward the pressure, fluid velocity and the ship’s total resistance. There are three kinds of skeg configurations: barge without skegs, skegs without deflection, and skegs with deflection. The barge was towed with forward speed were ranging across 3 knots – 9 knots. The simulations were conducted using an open-source RANS (Reynold Averaged Numerical Simulation) CFD code Open-FOAM. The simulations show that the skegs raise the barge’s resistance. The skegs with deflection have a bigger resistance amplification compared to skegs without deflection.